SWOT ANALYSIS IN THE DEVELOPMENT OF CULTURAL VILLAGE-BASED TOURISM VILLAGES - Festria Anita Yurnalis; Ummul Fithriyyah Mustiqowati (Yayasan Wayan Marwan Pulungan, 2023)
The purpose of this study is to determine the most suitable development strategy for a tourism village based on cultural villages in Nagari Jawi-jawi. This qualitative descriptive study uses SWOT analysis to collect data from informants. The author uses observations, interviews, and documentation with research informants, including the Tourism and Culture Office of Solok Regency, Wali Nagari Jawi-jawi, Nagarai Jawi-jawi Tourism Awareness Group, and important figures. The results of this study state that the Nagari Jawi-jawi cultural village has a lot of natural, cultural and man-made potential that can be developed to improve the Nagari Jawi-jawi economy and increase people's income. One approach that can be used based on the SWOT analysis is to provide attractive and unique tour package solutions with the aim of being different from other similar tourist villages. However, in its development there are obstacles in the form of lack of public awareness, limited funds and also low competitiveness.